Arduino-Based Robot Car for Returning Food Orders - Ahmad Munauwar, Ahmad Amir Fahmi; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2022)
This paper describes several Bluetooth innovative features, mobile and robot components, and to control a robot using a mobile phone through a wireless connection. To manage the motions of the car in small restaurants and minimize face-to-face interaction between customers and diners. This project also focused on creating and controlling remote control cars utilizing Arduino UNO, Bluetooth and smartphones. The purpose of this paper is to design the robot car that will deliver back orders to kitchens in restaurants in the range of 20 meters to 30 meters by implementing a smartphone as a medium to control the movement of the car by designing an Android Remote Control Bluetooth car application using MIT App Inventor Bluetooth connection. The connection range of the Bluetooth is recorded and tabulated so that the optimum distance reached by the Bluetooth car and the average speed of the Bluetooth car can be obtained by taking the average of the trials. The result is then plotted using Microsoft Excel to analyze the performance pattern of the graph obtained. From the collected data, the maximum distance reached by the Bluetooth to be controlled is 29.45 meters with 25.35 seconds taken to reach the distance. The average distance and average speed of the Bluetooth car are calculated using a mathematical method which are 28.48 meters and 1.16 m/s respectively. In conclusion, this RC Bluetooth car is practically safe and applicable to be used in a small restaurant since the Bluetooth coverage range is reachable and the speed of the car is considered as the normal speed with no load.